2020
DOI: 10.1183/13993003.00414-2020
|View full text |Cite
|
Sign up to set email alerts
|

EmPHasis-10 as a measure of health-related quality of life in pulmonary arterial hypertension: data from PHAR

Abstract: IntroductionWhile the performance of the emPHasis-10 (e10) score has been evaluated against limited patient characteristics within the United Kingdom, there is an unmet need for exploring the performance of the e10 score among PAH patients in the United States.MethodsUsing the Pulmonary Hypertension Association Registry, we evaluated relationships between the e10 score and demographic, functional, hemodynamics, and additional clinical characteristics at baseline and over time. Furthermore, we derived a minimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…The results from this study demonstrate that patients with CTEPH have higher E‐10 scores (worse HRQoL) at referral to a Pulmonary Hypertension Care Center as compared to patients with IPAH, but these differences do not persist over time in a large prospective multicenter cohort. While the differences in scores at baseline is statistically significant, it is smaller than the minimally clinically important difference reported for E‐10 scores, 32 which is approximately a six‐point change, so the clinical implications of the difference in scores remain to be determined. Among CTEPH patients, similar to what has been previously reported, 31 this study found that patients who undergo PTE have significant improvement in their HRQoL, and the improvement in scores may be more significant in patients without residual disease post‐PTE 4,5 …”
Section: Discussionmentioning
confidence: 87%
“…The results from this study demonstrate that patients with CTEPH have higher E‐10 scores (worse HRQoL) at referral to a Pulmonary Hypertension Care Center as compared to patients with IPAH, but these differences do not persist over time in a large prospective multicenter cohort. While the differences in scores at baseline is statistically significant, it is smaller than the minimally clinically important difference reported for E‐10 scores, 32 which is approximately a six‐point change, so the clinical implications of the difference in scores remain to be determined. Among CTEPH patients, similar to what has been previously reported, 31 this study found that patients who undergo PTE have significant improvement in their HRQoL, and the improvement in scores may be more significant in patients without residual disease post‐PTE 4,5 …”
Section: Discussionmentioning
confidence: 87%
“…21 In this European Respiratory Journal, Borgese et al confirm the correlation of emphasis-10-scores with other markers of disease severity, and that it serves as quantitative measure of patients overall perception of the impact of PAH on their life in a large collective of US-patients as retrieved by the pulmonary hypertension association registry (PHAR). 24 Additionally, this registry-based real-life analysis suggest for the first time a minimal important difference of the emphasis-10 of -6 points, as basis for further anchorbased validation. In second article in this European Respiratory Journal, Lewis et al describe in a large UK-multicenter study that emphasis-10 score are independent prognostic markers in patients with idiopathic and connective tissue disease associated PAH thus providing an additional value on top of currently used parameters and revealed a minimal detectable difference of 9 scores.…”
mentioning
confidence: 81%
“…Importantly, there was a much larger relative difference in the emPHasis-10 scores compared with SF-12 scores across each risk stratum, suggesting that a disease-specific tool such as emPHasis-10 is more sensitive to the differences in the risk status. The minimally important difference of emPHasis-10 has been suggested to be ∼6.0 points ( 15 ), and it is worth highlighting that the low- and high-risk groups’ scores differed by ∼10 points in this study. These findings are mirrored by a recent U.K. multicenter study that showed that the emPHasis-10 score predicted survival in PAH ( 16 ).…”
mentioning
confidence: 58%
“…This suggests that the emPHasis-10 score has the ability to integrate traditional clinical variables that are prognostic in PAH. Indeed, emPHasis-10 has been shown to correlate with World Health Organization functional class and 6-minute-walk distance ( 15 , 16 ).…”
mentioning
confidence: 99%